Coir and hop fibres: tensile characterization and comparison between fibres from distinct climates - Aguirar, Julia (2023)
Human behavior has significantly affected the climate. Because of that, the pursuit of new alternatives for non-renewable materials has increased. In that scenario, the use of natural fibre to substitute synthetic ones in composite materials has also increased. In this work, two types of natural fibres from different regions and climates were evaluated and compared. The evaluated fibres were Coir from Brazil and Hop from Portugal. Also were evaluated two different extraction methods for the hop batches, boiling in NaOH and maceration in water. To evaluate the composite mechanical characteristics, seven tensile tests were performed in each fibre batch, according to ASTM C 1557-14 – Standard Test Method for Tensile Strength and Young’s Modulus of Fibres, and the average tensile strength for each one was calculated. The highest value of ultimate tensile strength was brought by the hop extracted with the boiling in NaOH method and resulted in an average of 16 MPa.